Innovative integration of rural initiatives for participatory agricultural transformation (RIPAT) and farmer market school (FMS): a pathway to enhanced income and dietary diversity - Rogers Andrew Lumenyela; Emanuel Timothy Malisa; Christopher Paul Mahonge; Suzana Samson Nyanda (Cogent Food & Agriculture)
This study analyzed the factors contributing to the effectiveness of the combination of Rural Initiatives for Participatory Agricultural Transformation (RIPAT) and Farmer Market School (FMS) approaches on farmers’ income and dietary diversity. Data were analyzed using descriptive statistics, a multivariate multiple regression model, and content analysis. Village Saving and Lending Association (VSLA) membership, value-added practices, vaccination, improved feeds, improved seeds, irrigation, and collective marketing significantly influenced effectiveness. VSLA membership, improved feeds, and the use of improved seeds significantly influenced the effectiveness of these approaches. Therefore, stakeholders should promote collective marketing, digital platforms for market information, irrigation infrastructure and under take further research based on longitudinal or time series data to assess the long-term impacts of these interventions on income and food security.